2016
DOI: 10.1177/1557988315569298
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dysfunction and Sexual Behaviors in a Sample of Brazilian Male Substance Misusers

Abstract: The aim of this study was to evaluate the potential relationship between self-reported sexual dysfunction, sexual behavior, and severity of addiction of drug users. A cross-sectional design study was conducted at an inpatient addiction treatment unit in Sao Paulo, Brazil, with a sample of 508 male drug users. Sociodemographic data, sexual behavior, and severity of dependence were evaluated.The prevalence of sexual dysfunction was 37.2% and premature ejaculation was 63.8%. Men with sexual dysfunction presented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…Although some drugs can initially increase sexual response, particularly in those with previous sexual problems, the chronic use of substances tends to deteriorate all stages of sexual function in both male and female drug users [3][4][5] . In line with this evidence, a very high prevalence of sexual dysfunction was recently reported in association with substance use disorders in a Brazilian sample, with a significant correlation between sexual problems and the severity of drug use [6] .…”
Section: Introductionsupporting
confidence: 54%
“…Although some drugs can initially increase sexual response, particularly in those with previous sexual problems, the chronic use of substances tends to deteriorate all stages of sexual function in both male and female drug users [3][4][5] . In line with this evidence, a very high prevalence of sexual dysfunction was recently reported in association with substance use disorders in a Brazilian sample, with a significant correlation between sexual problems and the severity of drug use [6] .…”
Section: Introductionsupporting
confidence: 54%
“…A growing number of voices within the health behaviour field itself (e.g. Diehl et al, 2016; Katikireddi et al, 2013; Kaufman et al, 2014; Stetson et al, 2016) are echoing this sentiment. Of course one would expect disciplines such as psychology and medicine to remain central given the methodological and conceptual nature of HBIs; however, there is space also for incorporating more nuanced understandings of the social context in which HBIs take place.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have shown that the prevalence of sexual dysfunction is higher in men with substance dependence compared to men without [10,11]. A total of 40.9% of the men with substance abuse suffer from some kind of sexual dysfunction, with the most common being erectile dysfunction [11], which has a reported prevalence that is three times higher than in the general public [10]. Previous studies have shown that the long-term use of alcohol and opioids causes dysfunction in all the aspects of the individual's sexual function [8].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that substance dependence in men can affect sexual function and cause problems such as the lack of libido, erectile and orgasm dysfunction and even sexual violence [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%